Männerförderung im Kindergarten Die Maschine tuckert, aber sie läuft noch nicht - Koch, , Bernhard (innsbruck university press, 2016)
" ""More men in kindergarten"" as a blind spot in gender politics? The share of men in Austria's childcare facilities is less than 2%, in the educational institutions for kindergarten education about 4%. An increase in the proportion of men in elementary education is considered desirable by parents, kindergarten staff, educational science and politics in general. Not just for reasons of gender equality, but because children need women AND men. On the basis of an FWF research project carried out at the University of Innsbruck, this book presents basic conditions on the way to mixed-gender staff in kindergartens. The study results show strong persistence tendencies both in the system of childcare and in the gender equality system. Clear recommendations for measures to increase the proportion of men in kindergartens round off the contribution."